Pro-Kontra Ghibah dalam Tinjauan Hadis dan Konteks Maraknya Perilaku Gosip - Muhammad Luthfi Dhulkifli (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This paper addressed to cover both sides in case of gibah or gossip. It is important due to the fact that people often talk about others by their negativity. This paper focuses on Muslim hadith number 2589 as multi-interpreted hadith by its syarah (interpretation) that gives a proportion of both legal and prohibited. This paper tries to find in three points: quality of Muslim 2589 hadith, syarah, and the contextualization of hadith. To answer these questions, this research work on Yusuf Qaradhawis perspective i.e corresponding to the Quran; collecting other hadiths; linguistic analyzing; and contextualizing. In the end, Muslim 2589 hadith is a shahih hadith which is possible to do further research by its matan and the meaning. Although gibah is categorized as prohibited, there are several cases that make it legal such as asking for help or asking for fatwa and advice. Gibah or gossip should be abandoned regarding its negativity not only for others but also themselves